Investment entity of gold as a basis for efficiency gold mining - V. T. Borisovich; S. Yu. Gaganov (Известия высших учебных заведений: Геология и разведка, 2015)
In the modem economic conditions, gold is a unique investment instrument because of characteristics, such as the credit riskless and high liquidity, which is particularly important in times of economic and geopolitical tensions. The modern function of gold as object of investment, and also classical and modern instruments for investments into precious metal are considered: bars, coins, derivatives, warrants, unallocated accounts, depository receipts, E-gold, Exchange Traded Funds.